2014
DOI: 10.1074/jbc.m113.535898
|View full text |Cite
|
Sign up to set email alerts
|

Conopeptide Vt3.1 Preferentially Inhibits BK Potassium Channels Containing β4 Subunits via Electrostatic Interactions

Abstract: Background: BK channel function is differentially modulated by tissue-specific ␤ (␤1-4) subunits. Results: Conopeptide Vt3.1 preferentially inhibits neuronal BK channels containing the ␤4 subunit. Conclusion: Electrostatic interactions between Vt3.1 and the extracellular loop of ␤4 decrease voltage-dependent activation of the channel. Significance: Vt3.1 is an excellent tool for studying the structure, function, and roles in neurophysiology of BK channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Alternatively, it is possible that β4 subunits control BK channel function through their ability to restrict plasma membrane localization of BK α tetramers (see Section 2.3); in this scenario, BK β4 may be highly expressed but retained within the endoplasmic reticulum and not present in plasma membrane BK channels (Shruti et al, 2012). Martentoxin and conopeptide Vt3.1 were reported to preferentially inhibit β4-containing BK channels and could help provide novel insights into this question, but, as for iberiotoxin, the ratio of β4 subunits required to drive increased sensitivity to these inhibitors remains to be determined (Li, Chang, et al, 2014; Shi et al, 2008). …”
Section: Expression Patterns Of Bk Channel Subunits In the Cnsmentioning
confidence: 99%
“…Alternatively, it is possible that β4 subunits control BK channel function through their ability to restrict plasma membrane localization of BK α tetramers (see Section 2.3); in this scenario, BK β4 may be highly expressed but retained within the endoplasmic reticulum and not present in plasma membrane BK channels (Shruti et al, 2012). Martentoxin and conopeptide Vt3.1 were reported to preferentially inhibit β4-containing BK channels and could help provide novel insights into this question, but, as for iberiotoxin, the ratio of β4 subunits required to drive increased sensitivity to these inhibitors remains to be determined (Li, Chang, et al, 2014; Shi et al, 2008). …”
Section: Expression Patterns Of Bk Channel Subunits In the Cnsmentioning
confidence: 99%
“…But the binding between slotoxin and the BKα/β4 channel seemed to be irreversible in an unknown mechanism (Garcia-Valdes, Zamudio, Toro, & Possani, 2001). In contrast, martentoxin (Shi et al, 2008; Tao, Shi, Liu, & Ji, 2012) and conopeptide Vt3.1 (Li et al, 2014) were identified as the more selective blockers for the BKα/β4 channel, but not BKα/β1 channel, when compared with BKα channel alone. The β subunits were also reported to regulate BK channel modulation by ethanol.…”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…So crude extracts of these toxins can be safely used in animal models. The conopeptide Vt3.1 preferentially inhibited the BK channels containing the α + β4 subunits [87]. …”
Section: Bkβ (Kcnmb) Chainsmentioning
confidence: 99%